A Simulation Analysis of Factors Influencing the Attractiveness of Group Technology Cellular Layouts - Morris, John S.; Tersine, Richard J. (Management Science, 1990)
Group Technology (GT) is a multi-faceted approach to batch production that includes the reconfiguration of plant equipment from a functional layout to a series of product-oriented layouts that are referred to as manufacturing cells. The cells are dedicated to process families of parts that have similar machine operations. The purported benefits of GT over traditional functional layouts range from reduced work-in-process inventory and throughput times to increased worker satisfaction and productivity. However, recent simulation studies challenge some of these claims of superior performance for cellular layouts. This research examines the influence that factors in a firm's operating environment have on the performance of cellular layouts. A simulation model using hypothetical shop data is used to compare a process layout to a cellular layout using mean throughput time and mean level of work-in-process inventory as performance measures. The operating variables analyzed are (1) the ratio of setup to process time, (2) transfer time of material between work centers, (3) demand stability, and (4) the flow of work within cells. None of the individual changes in levels of operating variables produced a clear advantage for cellular layouts. However, the results from these experiments were used to postulate an “ideal” environment for cellular layouts. This environment is characterized as having a high ratio of setup to process time, stable demand, unidirectional flow of work within a cell, and a substantial level of material movement times between process departments. When all of these conditions are present, the cellular layout outperforms the process layout on both performance measures.